Inactivation kinetics of Listeria monocytogenes and Salmonella enterica on specialty mushroom garnishes based on ramen soup broth temperature - Joelle K. Salazar; Megan L. Fay; Gregory Fleischman; Bashayer A. Khouja; Diana S. Stewart; David T. Ingram (Frontiers in Microbiology)
Recent listeriosis and salmonellosis outbreaks in the U.S. have been associated with consumption of specialty mushrooms, including enoki and wood ear. These mushrooms are commonly consumed in Asian dishes such as ramen noodle soup and are often used as raw garnishes. No current guidelines exist for the serving temperature of ramen broth in restaurants for safety. The objective of this study was to evaluate the inactivation of both Listeria monocytogenes and Salmonella enterica on enoki and wood ear mushrooms based on the ramen broth temperature. Fresh mushrooms were chopped into pieces, inoculated with four-strain cocktails of L. monocytogenes or S. enterica, dried at ambient conditions for 30 min, then placed into bowls. Ramen broth (i.e., pork bone broth, Tonkotsu) at initial temperatures of 60, 70, 80, 90, or 100°C was poured over the mushrooms, submerging them. The bowls were held at ambient conditions while the broth temperatures were monitored, and mushrooms were sampled at intervals up to 60 min. From the broth temperature profiles and the pathogen log reductions of each mushroom type, the non-isothermal log-linear model was used to obtain maximum inactivation rates. The maximum pathogen inactivation on both mushroom types occurred within the first 5 min, regardless of the initial broth temperature. Broth temperatures of 60 and 70°C resulted in reductions of only 1–3 log CFU/g (inactivation rates of 0.33–4.72 log CFU/g/min), while reductions of 4–5 log CFU/g (inactivation rates of 8.74–17.21 log CFU/g/min) were observed with 80°C broth. The use of 90 and 100°C broth resulted in higher reductions of >5 log CFU/g (inactivation rates of 8.56–28.08 log CFU/g/min). In all cases, surviving populations, often >2.4 log CFU/g, were observed after 60 min. The results from this study can assist in the development of guidelines on the safe serving temperature of ramen soup at restaurants.